Torture as tort : comparative perspectives on the development of transnational human rights litigation - Scott, Craig (Craig M.) (Hart Pub., 2001)
Should it be possible for a victim of a human rights violation in one country to bring a private law claim against the alleged perpetrators in the courts of another country? This text presents a collection of essays which address this question.